Feasibility of a pharmacist-facilitated medicines review intervention for community-dwelling Māori older adults - Joanna Hikaka; Carmel Hughes; Rhys Jones; Hunter Amende; Martin J. Connolly; Nataly Martini (Elsevier, 2021)
Background: Pharmacist-facilitated medicines review services have been postulated as a way to address current inequities in health outcomes between Māori and non-Māori. These interventions have been shown internationally to improve the appropriate use of medicines but remain underutilised in Aotearoa New Zealand (NZ). By reviewing the literature and engaging with key stakeholders, we developed an intervention, which included collaborative goal-setting, education and medicines optimisation, for testing in a feasibility study. Objective: To determine the feasibility (recruitment, intervention delivery, and data collection methods) of a pharmacist-facilitated medicines review intervention for Māori older adults, and proposed intervention outcomes. Methods: This study was reported in accordance with the CONSORT 2010 statement: extension to randomised controlled pilot and feasibility trials and the Consolidated criteria for strengthening reporting of health research involving indigenous peoples: the CONSIDER statement. Participant eligibility criteria were: Māori; aged 55-plus; community-dwelling; enrolled in a general practice in Waitematā District Health Board (Auckland, NZ). Consented participants engaged in a medicines education component (participant and pharmacist) and an optional medicines optimisation component (participant, pharmacist and prescriber). Outcomes measures included: the feasibility of data collection tools and methods, time taken to conduct the intervention and research processes; medicines knowledge, medicines appropriateness and quality of life (QoL); pharmacist recommendations and prescriber acceptance rate. Results: Seventeen consented participants took part in the intervention from December 2019-March 2020 with the majority (n = 12) recruited through general practice mail-outs. Data collection was feasible using the predetermined outcome measure tools and was complete for all patient participants. Pharmacist intervention delivery was feasible. A mean of 9.5 recommendations were made per participant with a prescriber acceptance rate of 95%. These included non-medicine-related recommendations. Conclusion: The feasibility testing of pharmacist-facilitated medicines review intervention developed for (and with) community-dwelling Māori older adults allows for intervention refinement and can be utilised for further studies relating to pharmacist services in primary care.